Pengaruh Ukuran Perusahaan, Struktur Modal, Profitabilitas & Leverage Terhadap Nilai Perusahaan (Studi Pada Sektor Infrastructure, Utilities & Transportation Periode 2013-2017) - GIRI PRABOWO, NAUVAL; HARTONO, ULIL (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract This study aims to determine the effect of firm size, capital structure, profitability and leverage to firm value. The type of research used is quantitative. Sampling technique using purposive sampling. Data collection is done through documentation from infrastructure sector company, utilities & transportation period 2013-2017 which listed on BEI. The type of this research is a quantitative research using purposive sampling method, in order to obtain the 22 companies that meet the criteria for the research sample. The data used is secondary data is documented from company annual report that obtained from BEI (www.idx.co.id) and official website of each company. Data were analyzed were multiple linear regression analysis and using IBM SPSS version 24. The result of this research indicates firm size, capital structure and leverage has no influence on firm value. Meanwhile, profitability has influence on firm value. Keywords: firm value, firm size, capital structure, profitability, leverage